البنية المجهرية وآلية الربط لملحومات القوس الكهربائي غير المتماثلة فولاذ الى نحاس (University of Thi-Qar Journal for Engineering Sciences, 2011)
The aim of this work is to study thebonding mechanism and the microstructure of copper to steel welded by shielded metal arc welding (SMAW). The electrodes that used are ECuSi and ECuSn8thenthe examination of microstructure by optical microscopic, it is clearly observed that the copper side are completely interfering with epitaxial growth when using ECuSn8 but the side of steel reveal interaction waves at the interface with nonepitaxial growth. Some of fine cracks observed at the interface with ECuSi. The use of ECuSn8 explain interfering fine blockes from the steel inside the fusion zone.